Development of Greenhouse Effect Teaching Tool to Develop Science Process Skills in Class VII Middle School Students on the Theme of Global Warming - Yulianah, Yulianah; Leksono, Suroso Mukti; El Islami, R. Ahmad Zaky (PENDIPA Journal of Science Education, 2025)
The purpose of this research is to create a greenhouse effect teaching tool in science learning on the theme of global warming to foster Science Process Skills (PPP) in students. The development model used is a 4- D development model which consists of four stages: define, design, develop, and disseminate. Product validation was carried out by science education experts and practitioner experts who showed the level of product validity with a value of 86.18% included in the "excellent" category. The implementation of the use of greenhouse effect props was carried out by grade VII students at one of the junior high schools in Serang City. The data of the student response questionnaire showed that the teaching aids were able to grow PPP with a score of 80.37% with the "very good" category. The results of this study prove that the use of teaching aids in science learning on the theme of global warming can help grow students’ PPP through practicum activities.